Correlation between the structural state and magnetoresistive properties of granular CoxAg100-x alloy thin films. (June 2020) - Shpetnyi, I.O.; Vorobiov, S.I.; Kondrakhova, D.M.; Shevchenko, M.S.; Duplik, L.V.; Panina, L.V.; Grebinaha, V.I.; Gorobets, Yu.I.; Satrapinskyy, L.; Luciński, T.
Abstract: Extensive investigations into structural, magnetotransport and magnetic properties of granular thin films with a thickness of 20 nm based on Co and Ag in a wide range of component concentrations were carried out: 17 ≤  x  ≤ 89 where x is at.% of Co. The samples were obtained by the method of electron beam co-evaporation using two independent electron guns at room temperature. The correlation between the structural-phase state and magnetotransport and magnetic properties was established by TEM method. The threshold of structural percolation in granular films was observed for x  ≈ 60%. At lower concentration x < 64%, the films had a phase composition of Ag (fcc) + Co (hcp) and were characterized by an isotropic giant magnetoresistance (GMR). The maximum GMR values of 7.2% and 7.5% in transverse and longitudinal geometry, respectively, were observed at x  = 55 at.%. For higher concentrations ( x  > 70%) the films demonstrated anisotropic magnetoresistance (AMR), which was assumed to be associated with the appearance of ferromagnetic interactions between the cobalt granules. Highlights: The influence of the structural phase state on the MR properties has studied. The films with a low concentration of Co ( x  < 34 at. %) has been in a superparamagnetic state. The threshold of structural percolation of granular films has observed at x Co ≈ 60 at.%. At a concentration of x Co  ≥ 70 at% an anisotropic magnetoresistance has observed. The maximum value of GMR in the as-deposited state has observed at the x Co  = 55 at%.